Anti-Myocardial Ischemia Reperfusion Injury Mechanism of Dried Ginger-Aconite Decoction Based on Network Pharmacology - Xie, Feng; Wu, Yuan-Yuan; Duan, Guang-Jing; Wang, Bin; Gao, Feng; Wei, Pei-Feng; Chen, Lin; Liu, A-Ping; Li, Min (Frontiers in Pharmacology, 2021)
Objectives: The purpose of this study is to predict the potential mechanism of DAD in treatment of MI / RI through network pharmacology and then verify it through experiments. Methods: The Chinese herbal medicine pharmacology data and analysis platform (TCMSP) were used to search and screen for the effective components of the DAD and to analyze the possible therapeutic targets. After using the disgenet database to obtain disease targets, the DAD inhibitory MI / RI targets were obtained. In addition, David database was used for GO and KEGG analysis. Finally, the protective effect of DAD on MI / RI was validated experimentally in vivo and vitro. Results: 80 targets and 16 chemical components of DAD were obtained. Gene enrichment analysis showed that these targets play an important role in cell apoptosis, mitochondrial damage, inflammation and other biological processes. And KEGG analysis showed that PI3K / Akt signaling pathway was the most abundant. In vitro studies showed that DAD could reduce the apoptosis rate of H9C2 cells injured by H / R and improve energy metabolism and In vivo studies have shown that DAD can reduce myocardial ischemia and hypoxia injury by activating PI3K / AKT / GS3Kβ signaling pathway. Conclusion: DAD may regulate the mitochondrial energy metabolism mainly through the PI3K / AKT / GSK-3β signal pathway. For MI / RI, DAD may be a promising treatment strategy.